2018
DOI: 10.1002/jbm.a.36315
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparison of CD4‐targeting lipid–polymer hybrid nanoparticles using different binding ligands

Abstract: Monoclonal antibodies and peptides are conjugated to the surface of nanocarriers (NCs) for targeting purposes in numerous applications. However, targeting efficacy may vary with their specificity, affinity, or avidity when linked to NCs. The physicochemical properties of NCs may also affect targeting. We compared the targeting efficacy of the CD4 binding peptide BP4 and an anti-CD4 monoclonal antibody (CD4 mAb) and its fragments, when conjugated to lipid-coated poly(lactic-co-glycolic) acid nanoparticles (LCNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The set of design variables has been expanded to include nanoparticle avidity because it has an impact on nanoparticle distribution 41 . Multidimensional search schemes give rigorous optimization a computational advantage over brute force methods that change one variable at a time.…”
Section: Discussionmentioning
confidence: 99%
“…The set of design variables has been expanded to include nanoparticle avidity because it has an impact on nanoparticle distribution 41 . Multidimensional search schemes give rigorous optimization a computational advantage over brute force methods that change one variable at a time.…”
Section: Discussionmentioning
confidence: 99%
“…S5A). However, because chol-but reduces nonspecific cell binding ( 34 ), we kept it in our formulations for the subsequent targeting and animal studies.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that conjugating an anti-CD4 monoclonal antibody (mAb) to our optimized cbLCNPs led to high specificity for CD4 + T cells ( 34 ). Here, we conjugated an anti-CD4 mAb to our Ing3A-cbLCNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations